Applicability of theory of planned behaviour in predicting intention to use digital coupons : some evidence from students of IIUM - Yakasai, Abubakar Mukhtar (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2014)
The aim of this research is to explore factors that predict intention to use digital coupons among the students of International Islamic University Malaysia (IIUM). Data were collected through distribution of structured questionnaire to 392 students of the IIUM. This research proposed a conceptual model based on the Theory of Planned Behavior (TPB) and Theory of Involvement to examine the relationships among attitude, subjective norm, perceived behavioural control and involvement on behavioural intention to use digital coupons. To test the factorial validity of the constructs and the goodness of the proposed hypothesized model, Factor Analysis and Structural Equation Modelling (SEM) were used. The findings of this research indicate that the Theory of Planned Behaviour that is extended to include Theory of Involvement can be applied to predict customers' intention to use digital coupons in Malaysia. The empirical finding of this research supported three out of the four propositions in this research. It was found that attitude, subjective norm and involvement were shown to significantly predict intention to digital coupons. Interestingly, perceived behavioural control was not significantly related to the customers' (students') intention to use digital coupons. The findings of this research are valuable assets for marketing managers who are interested in using digital coupons as an alternative sales promotion tool both in the short and in long run especially among youth consumers in Malaysia. Academicians and researchers can also benefit immensely from this research and its findings.